A new shear strength criterion of three-dimensional rock joints - Li, Yingchun (2022)
The presence of rock joints substantially reduces the rock mass strength. The deformability and stability of natural and engineered rock structures, such as rock slopes and underground caverns, are highly afected by rock joints along which sliding can easily occur. Natural rock joints are inherently rough with randomly distributed asperities that control the shear behaviour. Predicting the shear strength of rough rock joints is crucial for the stability analysis and support design of rock-engineering structures.